Culturally Responsive Teaching Pemahaman Budaya pada Pembelajaran Teks Hikayat: Culturally Responsive Teaching (CRT) for Cultural Understandingin Hikayat Text Learning - Safitri, Linda; Wismanto, Agus (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Indonesia is the largest archipelagic country that has cultural diversity, both ethnicity, language, and religion. This diversity can be used as capital for integrating and understanding culture in the education system. In essence, education is the right of every Indonesian citizen, so that the learning process is expected to be carried out according to the interests, talents, and cultural background of each student. Such a learning process aims to equalize the cultural position of students and not create gaps or discrimination in each student. Thus, researchers were moved to apply the Culturally Responsive Teaching (CRT) approach for cultural understanding in learning saga texts with the subjects of grade X students at Semarang city high school. This approach is a learning approach that can be adapted to the cultural background of students. Learning with this approach is expected to introduce each other's culture between students so that cultural understanding can be produced without gaps and a sense of discrimination. Therefore, learning with this approach will create a safe and comfortable learning environment for each individual, especially in learning class X saga texts at Semarang city high school.